Synthesis of a Small Cyclic Frustrated Phosphane/Borane Lewis Pair - Ugolotti, Juri; Kehr, Gerald; Daniliuc, Constantin G.; Erker, Gerhard (Synthesis, 2017)
Treatment of pyrrolidinodivinylphosphane with three molar equivalents of bis(pentafluorophenyl)borane resulted in the formation of a bicyclic pyrrolidino-bridged P/B frustrated Lewis pair (FLP) derivative, isolated as its P–[HB(C6F5)2] adduct. The system can be converted into an unbridged cyclic P/B frustrated Lewis pair derivative by the addition of pyridine.
Keywords: frustrated Lewis pair; hydroboration; boron; phosphorus; heterocycle